Heterogeneous Exposure Associations in Observational Cohort Studies: The Example of Blood Pressure in Older Adults. - Odden, Michelle C; Rawlings, Andreea M; Khodadadi, Abtin; Fern, Xiaoli; Shlipak, Michael G; Bibbins-Domingo, Kirsten; Covinsky, Kenneth; Kanaya, Alka M; Lee, Anne; Haan, Mary N; Newman, Anne B; Psaty, Bruce M; et al. (Am J Epidemiol, 2019)
Heterogeneous exposure associations (HEAs) can be defined as differences in the association of a exposure with an outcome among subgroups that differ by a set of characteristics. This manuscript intends to foster discussion of HEAs in the epidemiological literature, and present a variant of the random forest algorithm that can be used to identify HEAs. We demonstrate the use of this algorithm in the setting of the association of systolic blood pressure and death in older adults. The training set included pooled data from the baseline examination of the Cardiovascular Health Study (1989-1993), the Health, Aging, and Body Composition study (1997-1998), and the Sacramento Area Latino Study on Aging (1998-1999). The test set included data from the National Health and Nutrition Examination Survey (1999-2002). The hazard ratios ranged from 1.25 (95% CI: 1.13, 1.37) per 10 mmHg higher systolic blood pressure in men aged ≤67 years with diastolic blood pressure >80 mmHg, to 1.00 (0.96, 1.03) in women with creatinine <0.7 mg/dL and a history of hypertension. HEAs have the potential to improve our understanding of disease mechanisms in diverse populations, and guide the design of randomized controlled trials to control exposures in heterogeneous populations.